SISTEM INFORMASI PENGADUAN PRODUK HALAL UNTUK KLASIFIKASI LAPORAN DENGAN METODE C4.5 BERBASIS QR CODE (STUDI : LPPOM MUI JAWA TENGAH) - Abdul Rofiq; M Iklil Mustofa (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2019)
An agency is encouraged to be able to have a good information system for the agency itself. LPPOM MUI Central Java is an institution where in the classification of complaints reports are still carried out manually, there will be the possibility of human error in the classification process of the complaint report. And this will harm all parties involved. automatically and apply the C4.5 Algorithm for analyzing the results of classifying the complaint report data. And from each complaint report will be classified into 3 parts, namely mild, moderate and severe.